Rescue Stories in Sufis’ Devotion: Shifting Human-Animal Boundaries in Pakistan (1947-2015) - Riaz Ahmad; Dr. Lubna Akram (Journal of Religion and Society, 2025)
Rescue of humans from dangerous animals and vice versa has been a yardstick of devotion to Sufis, in the history of Pakistan. This study deals with stories that substantiate suchlike yardstick of devotion. Therefore, this article investigates how, celebrated through hagiographical literature, the devotion of Sufis historically revolves around their control and power over animals in rescue and repression stories. This article also demonstrates how dominance over animals kept on benefiting not only to humans from animals but also to animals from animals. Then, it also concerns with the display of unusual behavioral performance of animals that portrays the power of Sufis as intact. This research paper tackles the question how boundaries were remained shifting between humans and animals in the hagiographical depiction of rescue and repression stories? Keywords: Animals, Sufis, Rescue, Repression, Devotion, Boundaries